Stealth emulsion based on natural rubber latex, core-shell ferrofluid/carbon black in the S and X bands - Vinayasree, S.; Nair, Ajalesh Balachandran; Mani, Manoj; Archana, V. N.; Joseph, Rani; Mohanan, P.; Joy, P. A.; Anantharaman, M. R. (Nanotechnology, 2019)
A lossy dielectric with an appropriate magnetic property is one of the requirements of a stealth material. The thickness of the absorber and the corresponding bandwidth of absorption are also other deciding factors that determine the choice of the material as microwave absorbers. A stable emulsion, which is lossy as well as magnetic, is promising, since it can be coated on surfaces with required thickness in the desired band. A magnetic nanofluidic emulsion serves the purpose. A microwave absorbing emulsion based on natural rubber latex with core-shell magnetic nanoparticles, based on superparamagnetic iron oxide nanoparticles (SPIONs), was developed. The effect of additives like carbon black on the bandwidth of absorption was also studied as a function of weight percentage of carbon black. The complex dielectric permittivity and magnetic permeability were evaluated using a vector network analyser in the S and X bands. Furthermore, these results were modelled using surface impedance equations. These investigations revealed that the incorporation of carbon black enhances the bandwidth of absorption and an emulsion with the required dielectric permittivity and magnetic permeability can be tailored for stealth applications.
Keywords: carbon black; core-shell nanoparticles; ferrofluid; microwave absorbing paint; natural rubber latex

Carbon black and chitin nanofibers for green tyres: preparation and property evaluation - Mathew, Mariya; Dominic, C. D. Midhun; Neenu, K. V.; Begum, P. M. Sabura; Dileep, P.; Kumar, T. G. Ajith; Sabu, Akshay Alax; Nagane, Dhiraj; Parameswaranpillai, Jyotishkumar; Badawi, Michael (Carbohydrate Polymers, 2023)
This research highlights the synergistic use of carbon black (CB) and chitin nanofibers (CHNFs) for developing green tyres for the first time. The CHNFs (12-30 nm) were prepared from chitin powder with the help of steam explosion and mild oxalic acid hydrolysis. The CHNFs were uniformly dispersed in natural rubber (NR) latex, dried, and mixed with CB in a two-roll mill to form NR/CB/CHNF composites. The NR/CB/CHNF composite at 1 phr CHNF loading exhibited tensile and tear strengths that were about 47 and 160 % greater than the NR-Neat, respectively. The dynamic mechanical analysis showed that the loss tangent (tan delta) at 60 degrees C was 50 % lower for the NR/CB/CHNF 1.0 composite than for the NR/CB50 composite. The study succeeded in developing a new green tyre tread formulation that would be helpful for attaining sustainability and a circular economy.
Keywords: carbon black; Chitin nanofibers; Green Tyre; natural rubber latex